Plant-Based Mediation Contribution to the Settlement of Cases at the Court - Abdul Mustopa (UIN Sunan Gunung Djati Bandung, 2020)
Mediation is one of the stages in the trial process. Mediation must be carried out by the parties, who are disputing civil cases in all areas of the judiciary. Mediation is a law, as the State of Indonesia is a state based on law. Article 1 of the 1945 Constitution is a constitution that regulates the form of the state of Indonesia as a constitutional state. The contribution of offline and online-based mediation to the settlement of cases in the regional courts of the Mataram Religious High Court when combined, the two seem to be insignificant in resolving cases, both offline and online mediation. The low level of success is due to the mediator factor and the factor of justice seekers. The mediator factor is assessed due to the lack of ability (skills) of the mediator, the mediator only carries out mediation according to formal legal principles, the mediator does not master role knowledge, communication science, family psychology which results in rigidity in carrying out mediation, if the mediator has multiple disciplines, of course it will spawn. better results of the implementation of mediation. The justice seeker factor is judged due to the lack of seriousness in participating in a mediation forum led by a mediator and each of them has adhered to its principles.